Restrictions on property rights on immovable cultural heritage - Čelić, Duško (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
The paper presents the specific legal nature of cultural goods, and from that aspect, the specific and numerous restrictions on property rights. As a special kind of object, which have special quality, functions and purpose in society, cultural goods are the object of a special real law arrangement. Such, especially real legal regulation, in the case of cultural goods, is the result of the coexistence of individual ("private") and public (social) interest in preserving cultural heritage as a general good of society. Restrictions on property rights on immovable cultural heritage, represent a specific concretization of the social attachment of property rights. As the main source of cultural property rights in the Republic of Serbia, the Law on Cultural Heritage, passed more than a quarter of a century ago, regulates the area of ​​property rights on cultural goods incompletely and imprecisely, even in conflict with later regulations, the Constitution and the Law on Public Property. Numerous provisions on the rights and obligations of the owners of immovable cultural property are incomplete and imprecise and guarantees of property rights are insufficient. The paper also raises the issue of cultural property rights and property restrictions on immovable cultural heritage, which are at the same time worship temples, whose owners and users are churches and religious organizations (res sacrae). It is necessary to adjust the property restrictions of the owners of these immovable cultural херитаге, to the specific needs of churches and religious organizations, as well as to further limit the possibility of encroachment on the right of ownership by public authorities.
Keywords: immovable cultural heritage, restrictions on property rights, right of pre-emption, expropriation, res sacrae.